Wheat Landraces Are Better Qualified as Potential Gene Pools at Ultraspaced rather than Densely Grown Conditions. (11th May 2014) - Ninou, Elissavet G.; Mylonas, Ioannis G.; Tsivelikas, Athanasios; Ralli, Parthenopi; Dordas, Christos; Tokatlidis, Ioannis S.
Abstract : The negative relationship between the yield potential of a genotype and its competitive ability may constitute an obstacle to recognize outstanding genotypes within heterogeneous populations. This issue was investigated by growing six heterogeneous wheat landraces along with a pure-line commercial cultivar under both dense and widely spaced conditions. The performance of two landraces showed a perfect match to the above relationship. Although they lagged behind the cultivar by 64 and 38% at the dense stand, the reverse was true with spaced plants where they succeeded in out-yielding the cultivar by 58 and 73%, respectively. It was concluded that dense stand might undervalue a landrace as potential gene pool in order to apply single-plant selection targeting pure-line cultivars, attributable to inability of plants representing high yielding genotypes to exhibit their capacity due to competitive disadvantage. On the other side, the yield expression of individuals is optimized when density is low enough to preclude interplant competition. Therefore, the latter condition appears ideal to identify the most promising landrace for breeding and subsequently recognize the individuals representing the most outstanding genotypes.